HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KECEMASAN PADA PASIEN PRE OPERASI KATARAK DI RUANG KENANGA RSUD dr. H. SOEWONDO KENDAL - Dewi Nurahayu; Sulastri Sulastri (Jurnal Surya Muda, 2019)
Nurse caring behavior is an act of caring for nurses for patients to fulfill their basic needs. The purpose of this study was to determine the relationship between nurses' caring behavior and the level of anxiety in pre-cataract surgery patients in the Kenanga room at the RSUD Dr. H. Soewondo Kendal. This research method is analytic with Cross Sectional approach. The sample in this study were 60 respondents, namely patients with cataract surgery with a age range of 50- 60 years old. The sampling technique in this study was accidental sampling. Data collection used the Hamilton Rating Scale for Anxiety and Caring Behavior Assessment Tool questionnaire. The results of univariate analysis showed that 66.7% of nurses 'caring behaviors were still in the low category and 55% of patients' anxiety levels were preoperative in the normal category. Bivariate analysis shows that the p-value is 0.001 (p <0.05). So that it can be concluded that there is a significant relationship between nurses' caring behavior and the level of anxiety in pre-cataract surgery patients in the Kenanga room at the RSUD dr. H. Soewondo Kendal. Based on the results of the study, it was suggested that the Hospital improve caring nurses so that patients who would be able to surgery were able to reduce their anxiety, through the provision of caring regulations, time discipline, and sanctions for nurses who had low caring behavior.